Impact of Social Media on communication of scientific concepts of first generation graduate learners in Kurinjipadi Village - Singaravelu , S. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The present study aims to find the impact of Social Media in effective communication of scientific concepts of first generation under graduate learners in kurinjipadi village. The investigator has used pretest-posttest control group experimental group design in the present study. The experimentation is conducted to the 1st year first students of Thiruvalluvar Arts and science college, Kurinjipadi. These students are coming from the nearby rural places and are learners who are aspiring to be 1st graduates in their family. Students who have the access to smart phones are only selected for the present study. The students are selected on the basis of their performance in pre-test. The students are divided into 2 groups viz control and treatment group. The groups are matched for mean and standard deviation. Both groups consist of 30 students each. Scientific Concepts test designed by the investigator is used assess the scientific concepts of 1st generation graduate learners. The tool consists of 25 multiple choice questions covering the topics including Waste management, pollution & climate change, Non-renewable energy resources, Information security education, Effect of plastic use and health and nutrition. Results revealed that subjects in the experimental group who are communicated using social media for two months have performed better on the scientific concepts test than the subjects of the control group. It may be said that Social Media has enabled them to improve their understanding of scientific concepts.